Pelatihan Pembelajaran Jarak Jauh Dengan Google Drive Dan Google Form Untuk Guru - Retnoningsih, Endang; Solikin, Solikin; Muis, Indra; Widiawati, Kristiana (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2021)
Abstract The learning process has shifted from conventional to technology-based. In line with the development of science, in the learning process there is a paradigm shift where the learning process must be oriented towards active learning students (student active learning). The teacher is expected to be able to present a fun learning process for students by using various learning media, so that the teacher must be creative in providing material to students. Learning media using google drive, bit.ly, and google forms are technology-based learning media that increases teaching and learning to be active and innovative with the internet. Therefore it is necessary to conduct training on making learning media using google drive, bit.ly, and google forms for teachers of SMAN 15 Bekasi City, so that they can improve their ability to implement distance learning in the adaptation period of new habits. The results of the implementation of the activity obtained an assessment of 55.2% which was Very Good in terms of material, participant responses, the relevance of the material to the participants' needs; 43.6% assessment has been good related to the material and presentation techniques; and 1.2% has had enough for one day of implementation, but it still needs additional time in providing training materials to see the participants' response was very good from this training activity. Keywords—ict; google; teachers; learning media; students. Abstrak Proses pembelajaran mengalami pergeseran dari konvensional menjadi berbasis teknologi. Sejalan dengan perkembangan ilmu pengetahuan maka dalam proses pembelajaran terjadi perubahan paradigma dimana proses pembelajaran harus berorientasi pada siswa belajar aktif (student active learning). Guru diharapkan dapat menghadirkan proses belajar yang menyenangkan bagi siswa dengan menggunakan berbagai media pembelajaran, sehingga guru harus kreatif dalam memberikan materi kepada siswa. Media pembelajaran menggunakan google drive, bit.ly, dan google forms merupakan media pembelajaran berbasis teknologi meningkat belajar mengajar menjadi aktif dan inovatif dengan internet. Oleh karena itu perlu dilakukan pelatihan pembuatan media pembelajaran dengan google drive, bit.ly, dan google forms untuk Guru SMAN 15 Kota Bekasi, sehingga dapat meningkatkan kemampuan dalam pelaksanaan pembelajaran jarak jauh di masa adaptasi kebiasaan baru. Hasil pelaksanaan kegiatan diperoleh penilaian 55.2% telah Baik Sekali dari sisi materi, respon peserta, keterkaitan materi dengan kebutuhan peserta; penilaian 43.6% telah Baik terkait materi dan teknik penyajian; dan 1.2% telah cukup selama satu hari pelaksanaan, namun masih perlu waktu tambahan dalam pemberian materi pelatihan melihat respon peserta yang Baik Sekali dari kegiatan pelatihan ini. Kata kunci— ict; google; guru; media pembelajaran; siswa.